International Journal of Mechanics and Materials in Design - Meguid, Shaker A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
It is the objective of this journal to provide an effective medium for the dissemination of recent advances and original works in mechanics and materials' engineering and their impact on the design process in an integrated, highly focused and coherent format. The goal is to enable mechanical, aeronautical, civil, automotive, biomedical, chemical and nuclear engineers, researchers and scientists to keep abreast of recent developments and exchange ideas on a number of topics relating to the use of mechanics and materials in design. Analytical synopsis of contents: The following non-exhaustive list is considered to be within the scope of the International Journal of Mechanics and Materials in Design: Intelligent Design: Nano-engineering and Nano-science in Design; Smart Materials and Adaptive Structures in Design; Mechanism(s) Design; Design against Failure; Design for Manufacturing; Design of Ultralight Structures; Design for a Clean Environment; Impact and Crashworthiness; Microelectronic Packaging Systems. Advanced Materials in Design: Newly Engineered Materials; Smart Materials and Adaptive Structures; Micromechanical Modelling of Composites; Damage Characterisation of Advanced/Traditional Materials; Alternative Use of Traditional Materials in Design; Functionally Graded Materials; Failure Analysis: Fatigue and Fracture; Multiscale Modelling Concepts and Methodology; Interfaces, interfacial properties and characterisation. Design Analysis and Optimisation: Shape and Topology Optimisation; Structural Optimisation; Optimisation Algorithms in Design; Nonlinear Mechanics in Design; Novel Numerical Tools in Design; Geometric Modelling and CAD Tools in Design; FEM, BEM and Hybrid Methods; Integrated Computer Aided Design; Computational Failure Analysis; Coupled Thermo-Electro-Mechanical Designs. Experimental Mechanics in Design: Advanced Mechanical Testing in Design; Non-destructive Tools in Design; Condition Monitoring in Design; Interferometry; Photoelasticity and Strain Gauges in Design; Quality Assurance and Control; Intelligent Sensors in Design. Design Case Studies: Aeronautical and Automotive Engineering; Mechanical Engineering; Chemical Engineering; Nuclear and Chemical Engineering; Civil Engineering; Bioengineering and Biotechnology.
Keywords: Mechanics; Engineering design; Materials science; Solid Mechanics; Classical Mechanics; Characterization and Evaluation of Materials; Engineering Design